An Analysis of Noun Phrases in Motorcycle Brochures - Muhammad Kemal Jatnika Almuharam (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2021)
The main objective of this study is to analyze the use of noun phrase and identify noun phrases that are frequently used. The present study applied the theory of Greenbaum, S & Nelson, G (2002) which divides the structures into seven types: determiner + noun, pre-modifier + noun, determiner + pre-modifier + noun, noun + post-modifier, determiner + noun + post-modifier, pre-modifier + noun + post-modifier, and determiner + pre-modifier + noun + post-modifier. Since all of the data are in a form of a descriptive text, method of textual analysis applied to analyze the data. The result of the study showed there were 796 noun phrases found from 10 brochures and 2 additional descriptions and they were classified into determiner + noun (19%), pre-modifier + noun (29%), determiner + pre-modifier + noun (47%), noun + post-modifier (1%), determiner + noun + post-modifier (0,88%), pre-modifier + noun + post-modifier (0,75%), determiner + pre-modifier + noun + post-modifier (0,25%). The final result show that the most frequently noun phrase used is the category 3 with structure determiner + pre-modifier + noun (47%), and the second one is the category 2 with structure pre-modifier + noun (29%).